"Believe me when I swear, for I cannot tell a single lie": Teofilo Folengo's Calculated Publishing Strategies.1. (June 2016) - Du Verger, Jean
Abstract : While analysing the subtle and intricate paratextual and peritextual features displayed in and around Teofilo Folengo's Baldus (1517), the present paper ventures to show how Folengo shaped the reader's approach to his book using various publishing strategies. Moreover, the four versions of the text illustrate not only the author's desire to improve his work but also, as we shall see through a series of close readings, his concern to escape the Roman church's censorial policy in early modern Italy. Thus, as Folengo strives to erase his own name by using a number of pseudo-selves and a variety of ancillary materials he poses the perennial question of authorial intent suggesting, as Helen Smith and Louise Wilson astutely remark in Renaissance Paratexts (2011), that "paratextual reading could be seen as a more difficult, and more advanced, skill than the ability to read the text itself".